Multidecadal preindustrial methane variability can be explained by noise in the source–sink imbalance - Eric J. Mei; Gregory J. Hakim; Cristian Proistosescu; Thomas K. Bauska; Christo Buizert; Alexander J. Turner (Proceedings of the National Academy of Sciences, 2026)
Ice core records of preindustrial methane indicate variability of ± 30 ppb ( ± 5%) on multidecadal-to-centennial timescales. Previous work has attributed these excursions to low-frequency or episodic changes in methane sources due to large-scale climate variability (e.g., the Little Ice Age) or human activity. Here, we explore what source and sink dynamics are consistent with ice core variability and show that the preserved variability can arise solely from white noise fluctuations in the source–sink imbalance. A simple model driven by unforced random perturbations, when integrated by the methane lifetime and firn processes, produces synthetic ice core records that match the spectral features of observations. Thus, fast-varying sources or sinks previously assumed too transient to affect ice core variability, such as weather-driven fluctuations in methane oxidants and emissions (e.g., interannual wetland variability), can produce the observed variability. Given large structural uncertainty in methane budget dynamics, we expand our model to quantify how variability in atmospheric methane and its drivers changes with the assumed dominant timescale of source–sink imbalance variability. Our results show that any source–sink imbalance timescale shorter than a century is consistent with the ice core record. Shorter timescales imply greater atmospheric variability but require larger-amplitude source–sink imbalance fluctuations. A key consequence is that rapid preindustrial source–sink variability (timescales ≲ 1 y) could explain modern methane growth rate variability. Constraining methane source and sink dynamics with preindustrial ice core records could therefore provide more robust priors for evaluating modern methane trends.